A comparative study of carbonic anhydrase activity in lymphocytes from colorectal cancer tissues and adjacent healthy counterparts - Giulia Nannini; Viviana De Luca; Chiara D'Ambrosio; Andrea Scaloni; Antonio Taddei; Maria Novella Ringressi; Fabio Cianchi; Fabio Staderini; Clemente Capasso; Amedeo Amedei; Claudiu T. Supuran (Taylor & Francis Group, 2022)
Several carbonic anhydrase (CA, EC 4.2.1.1) isoforms play an essential role in processes connected to tumorigenesis, as they efficiently accelerate the hydration of carbon dioxide to bicarbonate and proton. In this context, examples are CA IX and CA XII, which were proved to be upregulated in many solid malignancies. On the other hand, cancer and the immune system are inextricably linked, and targeting the immune checkpoints recently was shown to efficiently improve the treatment of malignancies. In this study, we have investigated the expression of CA isoforms in tumour-infiltrating lymphocytes (TILs) that, according to the immunosurveillance theory, were suggested to have a crucial role in the development of colorectal cancer (CRC). T lymphocytes isolated from healthy surrounding mucosa showed a higher CA activity compared to those present in tumour and peripheral blood in the same patients. CA I and II were confirmed as enzyme isoforms involved in the process, as determined by proteomic analysis of corresponding TIL samples. These preliminary findings suggest a dysregulation of the local immune response in the CRC tissues and a loss of effective anticancer mechanisms mediated by CAs therein.